The Role of Company Size as a Moderating Variable in the Relationship Between Tax Avoidance, Political Connections and Corporate Governance - Desman Serius Nazara; Stellamaris Metekohy; Muhamad Irpan Nurhab; Aprilya Dwi Yandari; Roy Setiawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
With business size acting as a moderating variable, the goal of this study is to gather empirical data regarding the impact of political and corporate links on tax evasion. The manufacturing firms in the consumer products sector that were listed on the Indonesia Stock Exchange between 2017 and 2021 were the subject of this study. Purposive sampling is used to determine the sample. A total of 100 data samples from 20 firms over a 5-year period made up the study's sample size. the approach of data analysis that makes use of moderated regression analysis and multiple linear regression analysis. The findings demonstrate that institutional ownership and political ties have an impact on tax evasion, but independent commissioners and the audit committee have no impact. According to the results of the moderation test, business size can influence institutional ownership and independent commissioners but not audit committees or political links in terms of tax evasion.